2015
DOI: 10.1007/s12035-015-9102-9
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 Antagonist AMD3100 Suppresses the Long-Term Abnormal Structural Changes of Newborn Neurons in the Intraventricular Kainic Acid Model of Epilepsy

Abstract: Abnormal hippocampal neurogenesis is a prominent feature of temporal lobe epilepsy (TLE) models, which is thought to contribute to abnormal brain activity. Stromal cell-derived factor-1 (SDF-1) and its specific receptor CXCR4 play important roles in adult neurogenesis. We investigated whether treatment with the CXCR4 antagonist AMD3100 suppressed aberrant hippocampal neurogenesis, as well as the long-term consequences in the intracerebroventricular kainic acid (ICVKA) model of epilepsy. Adult male rats were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 91 publications
2
18
0
Order By: Relevance
“…These results suggested that changes in hippocampal newly-generated neurons may be closely related to the increased neuronal excitability in the recurrence of seizure activity in the TLE. Our results are consistent with early studies showing abnormal hippocampal neurogenesis in epileptic rats (28); however, the find that newborn neurons plasticity and excitability has not been reported previously.…”
Section: Discussionsupporting
confidence: 93%
“…These results suggested that changes in hippocampal newly-generated neurons may be closely related to the increased neuronal excitability in the recurrence of seizure activity in the TLE. Our results are consistent with early studies showing abnormal hippocampal neurogenesis in epileptic rats (28); however, the find that newborn neurons plasticity and excitability has not been reported previously.…”
Section: Discussionsupporting
confidence: 93%
“…Seizures can activate progenitor cells in the subgranular zone of the dentate gyrus in the hippocampus, and these newborn neurons integrate into the hippocampal circuitry and contribute to hippocampal network plasticity, thereby affecting epilepsy ( 25 , 26 ). Consistent with the findings in the present study, Song et al also found that newborn neurons exhibited abnormal dendritic development, including longer apical and basal dendrites, and were accompanied by long-term seizure activity in an intraventricular kainic acid model of epilepsy ( 27 ). Of note, the hippocampal neurogenesis and neuronal migration stimulated by SE were prominent at least within 28 days, which coincided with the finding in the latent phase in the present study ( 24 ).…”
Section: Discussionsupporting
confidence: 92%
“…Conditional deletion of Cxcr4 in MGE-derived INs causes their premature entry in the cortical plate and results in altered regional distribution of INs (Li et al, 2008). A recent study showed that the CXCR4 antagonist AMD3100 reverses some of the pathological landmarks of temporal lobe epilepsy (TLE) (aberrant neurogenesis and distorted dendritic morphology of newborn DG neurons), and that it significantly reduces the duration and frequency of chronic seizures in the intracerebroventricular KA model of epilepsy (Song et al, 2016). Interestingly, although CXCR4 has not been formally associated with epilepsy in humans, we recently described a young child with severe early-onset epileptic encephalopathy carrying a de novo 2q22.2q21.3 chromosomal deletion encompassing the CXCR4 gene (Michaud et al, 2014).…”
Section: Neuronal Locomotion Neurite Extension Neurite Branching Anmentioning
confidence: 99%